2018
DOI: 10.1007/s11307-018-1181-3
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Role of FDG-PET/CT in the Diagnosis, Staging, and Treatment of Breast Cancer

Abstract: The applications of 2-deoxy-2-[F]fluoro-D-glucose positron emission tomography/X-ray computed tomography (PET/CT) in the management of patients with breast cancer have been extensively studied. According to these studies, PET/CT is not routinely performed for the diagnosis of primary breast cancer, although PET/CT in specific subtypes of breast cancer correlates with histopathologic features of the primary tumor. PET/CT can detect metastases to mediastinal, axial, and internal mammary nodes, but it cannot repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
146
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(153 citation statements)
references
References 87 publications
4
146
2
1
Order By: Relevance
“…On the other hand, MRI had better performance when either of the two methods was used after the completion of neoadjuvant treatment, with significantly higher sensitivity (88% vs 57%) (19). There is a wide range of sensitivity and specificity across studies, which may be attributed to the heterogeneity between studies (17).…”
Section: Histological Examinationmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, MRI had better performance when either of the two methods was used after the completion of neoadjuvant treatment, with significantly higher sensitivity (88% vs 57%) (19). There is a wide range of sensitivity and specificity across studies, which may be attributed to the heterogeneity between studies (17).…”
Section: Histological Examinationmentioning
confidence: 98%
“…On the other hand, FDG-PET has been shown to have low sensitivity for small lesions (13). To date, several studies examined the role of PET/CT in predicting response to neoadjuvant chemotherapy when performed after the completion of neoadjuvant chemotherapy and before surgery, with inconsistent findings, most of them comparing the findings with that of MRI (6,(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Sonography is more widely used in clinical practice, albeit as a method of cancer screening rather than tumor size estimation (17). Positron emission tomography (PET)/computed tomography (CT) using 2-deoxy-2 fluoro-18-fluoro-D-glucose (18F-FDG) is a useful modality in the diagnosis of patients with breast cancer (18). By evaluating glucose metabolism, it can also be used in staging, restaging and post-therapeutic response evaluation (16,19).…”
Section: Introductionmentioning
confidence: 99%
“…By evaluating glucose metabolism, it can also be used in staging, restaging and post-therapeutic response evaluation (16,19). In a previous study, 18 F-FDG PET/CT was considered inappropriate for evaluation of tumor size and not recommended as a priority option in clinical practice due to its poor spatial resolution, which limits clear delineation of the tumor boundary (20). However, other studies have demonstrated the advantage of 18 F-FDG PET/CT in tumor size estimation (21).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular imaging modalities including whole-body 2-deoxy-2-18 F-fluoro-d-glucose ( 18 F-FDG) PET/computed tomography (CT) and positron emission mammography (PEM) have been evaluated for primary BC diagnosis, staging, and monitoring the response to therapy. 15 For years, the combination of PET and CT has offered concurrent anatomic and functional information in oncological imaging. In recent years, the integration of PET and MRI into a hybrid system has merged high sensitivity and metabolic characterization of PET with superior soft tissue characterization of MRI.…”
Section: Introductionmentioning
confidence: 99%